Soluble matrix protein is a potent modulator of mesenchymal stem cell performance - Yeo, Giselle C.; Weiss, Anthony S. (Proceedings of the National Academy of Sciences - PNAS, 2019)
We challenge the conventional designation of structural matrix proteins primarily as supporting scaffolds for resident cells. The extracellular matrix protein tropoelastin is classically regarded as a structural component that confers mechanical strength and resilience to tissues subject to repetitive elastic deformation. Here we describe how tropoelastin inherently induces a range of biological responses, even in cells not typically associated with elastic tissues and in a manner unexpected of typical substrate-dependent matrix proteins. We show that tropoelastin alone drives mesenchymal stem cell (MSC) proliferation and phenotypic maintenance, akin to the synergistic effects of potent growth factors such as insulin-like growth factor 1 and basic fibroblast growth factor. In addition, tropoelastin functionally surpasses these growth factors, as well as fibronectin, in allowing substantial media serum reduction without loss of proliferative potential. We further demonstrate that tropoelastin elicits strong mitogenic and cell-attractive responses, both as an immobilized substrate and as a soluble additive, via direct interactions with cell surface integrins αvβ3 and αvβ5. This duality of action converges the long-held mechanistic dichotomy between adhesive matrix proteins and soluble growth factors and uncovers the powerful, untapped potential of tropoelastin for clinical MSC expansion and therapeutic MSC recruitment. We propose that the potent, growth factor-like mitogenic and motogenic abilities of tropoelastin are biologically rooted in the need for rapid stem cell homing and proliferation during early development and/or wound repair.